Nietzsche and Ecological Reason(s) in the Anthropocene - Jörg, Kilian (The Trumpeter, 2020)
Ecosophical discourses around the ecological condition that is sometimes referred to as the “Anthropocene” require a fundamental rethinking of key concepts of occidental philosophy, including reason. Nietzsche’s body of work offers manifold tools for the rethinking of reason, and this paper seeks to apply them to achieve a “new ecological image of thought.” It will demonstrate 1) how there is a clear ecological awareness motivating Nietzsche’s affirmative critique of reason, 2) how one can find rudiments of a pluralization of the concept of reason in Nietzsche's body of work, as well as 3) traces of a new, qualitatively different form of ecological reason for the time called the Anthropocene – with all its problems and possibilities. In doing so, this paper will demonstrate how Nietzsche can be very productively applied to contemporary eco-philosophical discussions.